Communication as an Organization Shaper: Multi-Stakeholder Practices in an Indonesian MSME Empowerment Program - Alfiani, Sandra (Universitas Islam Negeri Raden Intan Lampung, 2026)
Government-facilitated MSME empowerment initiatives rely on multi-stakeholdercollaboration; however, the communication practices that underpin these collaborativeorganizations remain insufficiently examined. This study elucidates how stakeholdercommunication practices form and sustain the East Java Super Corridor Bojonegorocollaborative organization within the 2023 empowerment program. A qualitative single-casestudy was conducted, with data gathered through in-depth interviews with ten informants fromfive stakeholder categories and documentary analysis of program archives. The data wereanalyzed using pattern matching within the framework of the Communicative Constitution ofOrganizations. The findings indicate that communication actively shaped the organizationthrough four mechanisms: official texts with institutional authority, recruitment practicesestablishing stakeholder membership, WhatsApp-based coordination maintaining activityflows, and evaluation and market facilitation enhancing legitimacy. Moreover, this studyidentifies reconstitution flow as a temporal mechanism that sustains organizational continuitybetween program cycles. Communication also transformed products into more visible,credible, and market-ready branded objects. Finally, the study extends the theory of theCommunicative Constitution of Organizations to project-based public sector governance andrecommends considering communication infrastructure as a fundamental component inMSME empowerment programs.